A multidimensional procurement literacy instrument: Development and validation among undergraduate procurement students in Ghana - Priscilla Boafowaa Oppong; Daniel Ofori; Phanuel Wunu; Edmond Yeboah Nyamah; Evelyn Yeboah Nyamah; Justice K. G. A. Boateng; Gloria K.Q. Agyapong (PLoS ONE, 2026)
Procurement remains one of the central functions in public- and private sector governance, yet relatively little attention has been given to how procurement capabilities develop during undergraduate education. This study addresses this gap by developing and validating an instrument to measure Procurement literacy of undergraduate students in Ghana. Drawing on CIPS Global Professional Standards and other policy frameworks, this study initially conceptualised six domains of procurement literacy. The initial instruments were refined through expert review before being administered to a sample of 554 students from selected public universities. The structure and psychometric properties of the administered instruments were examined using exploratory and confirmatory factor analyses. In total, a 30-item instrument grouped into five domains emerged: Ethical Procurement Practice, Procurement Planning and Decision-Making, Supplier and Contract Management, Digital and E-Procurement competency, and Legal and Policy Knowledge. The final 30-item scale demonstrated strong internal consistency, satisfactory convergent and discriminant validity, and measurement invariance across academic levels. Predictive validity was examined using the intention of students’ behavioural intention to engage in ethical procurement practices, with all dimensions showing positive and statistically significant associations. Differences in procurement literacy were also observed at academic levels, with effect sizes ranging from small to moderate. Harman’s single-factor test (48.5%) indicated that common method bias was not a threat. The findings suggest that procurement literacy can be measured reliably at the undergraduate level and that the instrument offers a practical tool for curriculum evaluation, instructional planning, and early capability assessment in procurement education.